Finding True North in Ethical Practices in Information Service Provision in Academic Libraries in Uganda - Kaddu, Sarah B.; Ssekitto, Francis (Ghana Library Journal, 2023)
Ethical practices in information service provision have become integral for librarians and information professionals in the ever-evolving landscape of information dissemination and access. These practices encompass an array of principles governing professional behaviours, ensuring moral conduct, and preventing potential misconduct. This paper explores the ethical practices and information services in the Makerere University Business School (MUBS) library. This study adopted a qualitative research approach, with semi-structured interviews, observations, and document analysis as the data collection methods. The findings illuminated a comprehensive array of services available within the MUBS library context, including textbooks and eBooks short-term loans; reference books and e-reference books; internet and WIFI; current awareness; interlibrary loan; journals and e-journals access to patrons; MUBS librarians’ dedication to principles such as equitable access, privacy protection, and intellectual property rights. Ethical dilemmas arising from balancing intellectual freedom and responsible information provision are also unveiled. These findings resonate with global ethical considerations in librarianship, reflecting libraries’ evolving roles in the digital age. The study’s insights will inform MUBS library operations and contribute to the scholarly discourse on ethical library practices. The research implies that librarians’ ethical decisions impact service quality and user experiences.